Pengaruh Dimensi Fraud Triangle terhadap Potensi Kecurangan Akademik - Marta Karolina Purba; Dea Annisa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of the potential fraud triangle (pressure, opportunity and rationalization) on student academic cheating behavior in students of the accounting study program, Faculty of Economics and Business, Pamulang University. Academic fraud has become one of the most serious challenges in higher education, especially in the modern era which demands high academic achievement and superior competence. This research is a quantitative research method with data collection in the form of questionnaires distributed via google form, which is measured using a Likert scale ranging from 5-1. The population of this study were students 2nd to the 8th semester. The sampling method used in this study was convenience sampling with a sample size of 410 respondents, which was obtained from the results of distributing questionnaires through google form. The data analysis method used is multiple linear regression using SPSS version 24. The results of this study indicate that pressure, as a dimension of the Fraud Triangle, does not significantly affect the potential for academic fraud. However, opportunity and rationalization are shown to have a significant influence on the potential for academic fraud.